Posterior Interosseous Nerve Injury From Chronic Monteggia Fracture Dislocation Requiring Nerve Reconstruction - John Bartoletta, MD; Raymond Tse, MD; Suzanne Steinman, MD (Journal of the Pediatric Orthopaedic Society of North America, 2025)
Monteggia fracture-dislocations are rare elbow injuries in the pediatric population. Multiple case reports have described posterior interosseous nerve (PIN) palsies in the setting of Monteggia fracture-dislocations, usually due to stretch neuropraxia. In this report of a Bado Type III Monteggia fracture-dislocations with delayed diagnosis of an entrapped PIN, we highlight the importance of timely diagnosis. Surgical reconstruction using a sural nerve autograft was required when the PIN was found to be entrapped in the radiocapitellar joint and encircling the radial neck. Key Concepts: (1) Monteggia fracture-dislocations are rare elbow injuries in the pediatric population and can be missed. (2) The orthopaedic surgeon should have heightened suspicion for a posterior interosseous nerve palsy in Bado Type III Monteggia fracture-dislocations. (3) If a posterior interosseous nerve palsy is identified at the time of injury and reduction is difficult, we should consider nerve exploration as it may be entrapped in the joint.